Management of banana pseudostem weevil, Odoiporus longicollis (Olivier), using safe chemicals and bio-rational methods - Sivakumar T (Department of Agricultural Entomology, College of Agriculture, 2017)
A study on ‘Management of banana pseudostem weevil, Odoiporus longicollis (Olivier), using safe chemicals and bio-rational methods’ was conducted at the College of Agriculture, Vellayani and in farmer’s field during 2012-2015. The main objective was to evolve strategies for managing the pest using safe chemicals and bio-rational methods. The study involved documentation of the pest status and farmers’ management practices, evaluation of the efficacy of different insecticides, botanicals and bio-agents under laboratory and field conditions and determination of harvest time insecticide residues in edible parts. Status of pests in banana was documented from Alappuzha, Pathanamthitta, Kollam and Thiruvananthapuram districts during 2013. O. longicollis incidence in banana cv. Nendran varied from 5.36 per cent in Kollam to 7.64 per cent in Pathanamthitta. Erionota sp., Bactrocera dorsalis (Hendel), Polytus mellerborgi (Boheman), Coccus hesperidum L. were observed as the emerging pests from the area. Pest management practices adopted by banana farmers, documented from the above districts, revealed the use of sixteen types of pesticides, including organic preparations. No specific parasite or predator was recorded from field except earwigs and red ants. Efficacy of insecticides, botanicals and bio-agents for the management of O. longicollis was evaluated under laboratory conditions. Thiamethoxam (0.01%), emamectin benzoate (0.002%) and cartap hydrochloride (0.1%) caused 100 per cent mortality of adults and grubs of the pest within 36 h after treatment. Among the botanicals, cassava leaf distillate based formulation, ‘Nanma’ (5%) caused 36.67 per cent mortality of adults and grubs, whereas neem soap caused 36.67 and 16.67 per cent mortality of adults and grubs, respectively. Among the bio agents tested, Metarhizium majus Bisch, Rehner and Humber (ICAR-CPCRI) 2% caused 80 per cent mortality of grubs on the seventh day of inoculation. Compatibility of insecticides, fungicides and botanicals with M. majus was tested using poisoned media technique. The fungicides viz., propiconazole (0.1%), tebuconazole (0.1%), mancozeb (0.3%) and carbendazim (0.1%) resulted in total growth inhibition of M. majus, while thiamethoxam (0.01% and 0.03%), cartap hydrochloride (0.05%) and neem soap (1.0%) were found compatible. Application methods of insecticides, botanicals and bio-agents were standardised through field experiment at the Instructional Farm, College of Agriculture, Vellayani during 2013-2014. Among the application methods, leaf axil filling (LAF) and injection of thiamethoxam (0.01% and 0.03%) recorded a yield of 10.98 and 10.88 kg plant-1, respectively. In the case of biopesticides, the highest yield (6.43 kg plant-1) was recorded with swabbing + LAF application of M. majus (20g l-1), whereas among botanicals, spraying +LAF gave the highest yield (8.8 kg plant-1) for neem soap (1.0%) application. Prophylactic and curative methods for the management of the pest, using thiamethoxam, neem soap, cassava leaf based preparation and M. majus, were tested in farmer’s field at Konni, Pathanamthitta district during 2014-2015. In prophylactic method thiamethoxam injection (0.03%) at 5th and 6th months after planting recorded an yield of 10.67 kg plant-1, followed by thiamethoxam (0.01%) leaf axil filling (10.32 kg plant-1) at 5th and 6th months after planting. Significantly higher value for BC ratio (2.44) was recorded for thiamethoxam (0.03%) injection. The BC ratio was 2.33 for thiamethoxam (0.01%) leaf axil filling. Application of M. majus (2%) at five months after planting, followed by thiamethoxam LAF (0.01%) at 6th month after planting yielded 8.82 kg plant-1. In curative method, plant survival was the highest (80 per cent) for thiamethoxam injection (0.03%). However, a low BC ratio of 0.86 was observed. Thiamethoxam injection (0.03%) and leaf axil filling (0.01%) were on par with chlorpyrifos (0.03%), as curative method. No detectable residue of thiamethoxam on any edible parts of the plant was observed at the time of harvest. To conclude, ‘Nendran’ was found to be the most susceptible banana cultivar to O. longicollis. Thiamethoxam at 0.01 per cent and 0.03 per cent were compatible with the entomopathogen, M. majus. Prophylactic method using thiamethoxam injection @ 0.03% and leaf axil filling @ 0.01%, both at five and six months after planting, were found effective, eco friendly and economical practice for O. longicollis management. The application of entomopathogenic fungi M. majus at five months after planting followed by thiamethoxam (0.03%) injection at six months after planting was also effective for managing the pest.